ANALISIS HORIZONTAL TERHADAP KINERJA KEUANGAN PT.DELTA DJAKARTA TBK. PERIODE 2022 – 2023 TRIWULAN II - Anggita Arsyikirani; Khanza Monica Salsabila; Shafira Ayu Rachmawati; Tanaesya Suhendro; Fakhmi Zakaria (Jurnal Akuntansi, Ekonomi dan Manajemen Bisnis, 2024)
This article aims to conduct a financial ratio analysis at PT. Delta Jakarta Tbk., a company listed on the Indonesia Stock Exchange, during the second quarter of 2022-2023. Financial ratio analysis is an important approach in evaluating a company's financial performance, providing a comprehensive picture of the sustainability and operational efficiency of the company. This research methodology involves collecting financial data from the quarterly financial statements of PT. Delta Jakarta Tbk. during the period 2022-2023. The financial ratios analyzed include liquidity ratios, profitability ratios, solvency ratios, and activity ratios. This data is then analyzed to identify trends, strengths, and potential risks that might affect a company's financial performance. The results of this analysis are expected to provide in-depth insight into the financial condition of PT. Delta Jakarta Tbk. as well as providing a better outlook to stakeholders, including investors, financial analysts and company management. This article can also be an important reference for financial researchers and practitioners who are interested in understanding the financial performance of companies in the Indonesian capital market.